Hubungan Metode Demonstrasi Terhadap Kecerdasan Interpersonal Anak Di Paud Al-Jannah Sowan Kidul Kedung Jepara Jawa Tengah - Tiyas Syarifatul Hilmy; Salis Khoiriyati; Dwi Bhakti Indri M (Atthiflah: Journal of Early Childhood Islamic Education, 2020)
Interpersonal intelligence is the ability to know what someone is thinking, someone's behavior. To be able to help develop children's interpersonal intelligence, a suitable method is needed. An example of the method is the demonstration method. This research has a problem formulation is whether the demonstration method has a relationship to the interpersonal intelligence of children in Paud Al-Jannah. Research that is taken using quantitative research using survey methods and descriptive approaches. From the results of this study, from 26 children, on the criteria to develop according to expectations, there were 22 children who got an average score of 65.2% and 4 children who entered the criteria of starting to develop got an average score of 42.5%. Based on these data, the conclusion that interpersonal intelligence in Paud Al-Jannah has very well developed criteria has an average value of 84.7% for the total number. So it is very important in teaching children a method. An example of the method is the demonstration method. With this method, the method is to teach it by demonstrating something and showing children directly a process